Жадьылӥсь мешок: выжыкылъёс / Вениамин Ившин - Ившин Вениамин Никонорович (Удмуртия, 2012)
Экземпляры: ф.5 (20150209) / Инвентарный номер: 56302 / Цена: 302.00 / Сис.шифр: 84(2Рос=Удм)6 / Авт.знак: И 25 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Удм)6